EFFECT OF EXTRACTION METHODS ON PHENOLIC CONTENT AND ANTIOXIDANT ACTIVITY OF BAJAKAH ROOT (Spatholobus littoralis) - Agustin, Julia Then; Kambira, Pretty Falena Atmanda; Michael, Michael; Prismawan, Deka (Indonesian Journal of Health Science, 2025)
The Bajakah root (Spatholobus littoralis), a native plant of Kalimantan, is recognized for its phenolic content and antioxidant activity. This study aims to compare the effects of three extraction methods—maceration, soxhlet, and reflux—on the total phenolic content and antioxidant activity of Bajakah root extracts. The plant material was extracted using 96% ethanol, followed by phenolic content analysis via the Folin-Ciocalteu method and antioxidant activity evaluation using the DPPH assay. Results revealed that the reflux method produced the highest phenolic content (17.6 ± 0.1 mg GAE/g extract) and the strongest antioxidant activity (IC50 of 26 ± 1 µg/mL). The soxhlet method yielded a phenolic content of 17.4 ± 0.2 mg GAE/g extract with an IC50 of 30 ± 0 µg/mL, while maceration resulted in the lowest phenolic content (14.6 ± 0.7 mg GAE/g extract) and an IC50 of 34 ± 2 µg/mL. The heating processes involved in the reflux and Soxhlet methods likely facilitated the degradation of glycosides, thereby enhancing phenolic content. All methods demonstrated exceptionally strong antioxidant activity (IC50 < 50 µg/mL). This study underscores the significant influence of extraction methods on the phenolic quality and antioxidant capacity of Bajakah root extracts.